Improving Evidence‐Based Surveillance System: Foodborne Disease Outbreak in Oyibi - Esther Priscilla Biamah Danquah; Kwame Adu Okyere Boadu; Jeffrey Kojo Arhin; Martha Nabila; Akua Addy; Shadrack Darko; Bright Osei (Health Science Reports)
ABSTRACT Background Foodborne illness and foodborne injury can be severe and fatal and have a negative impact on human health over the long‐term period. On January 20, 2023, an unknown number of people had purchased and consumed “waakye or rice” with salad, stew, meat, gizzard, egg, among others from a food vendor at Oyibi, located in the Kpone‐Katamanso Municipality in the north eastern outskirts of Accra. The disease had reportedly killed one person within 72 h after consumption of the meal and affected 53 other people. The cause or mode of transmission of this was unknown; therefore, it had to be ascertained. The additional fact that the illness had the potential to affect many more people necessitated this study to be done. Methods The investigation was a cross‐sectional epidemiological study conducted in Oyibi and its environs in the Kpone‐Katamanso Municipality and the Adenta Municipality. Anybody who ate food from the food vendor at Bush Canteen in Oyibi and presented with vomiting or diarrhea or abdominal cramps from January 22 to February 2, 2023 was studied. Permission was sought from the municipal assembly and municipal health directorate for this study. Results Of the 62 persons who ate the food contacted, only 59 of them developed signs and symptoms and reported to a health facility. The population of the municipality is 426,098, making an attack rate 0.015% with one mortality (1.7%) case fatality. The study was a point source outbreak with an incubation period of 2 h minimum to 56 h maximum at an average of 15 h. Chlorpyrifos (33.4ppb) was detected in the stored tomato stew. E. coli, Bacillus cereus, and Clostridium perfringens detected in these samples were less than 10 cfu/g. Staphylococcus spp. was isolated from both implicated tomato stew (100,000 cfu/g) and stored stew (500,000 cfu/g). Conclusions An outbreak of foodborne illness was established at Oyibi Kpone Katamanso Municipality in the Greater Accra Region. The outbreak was a point source which started on January 20, 2023. It was established that people who ate stew, waakye, macaroni and plantain were more likely to fall ill, and the stew was a possible source of the outbreak.